The Perception of Students EFL Class in English Language Learning after Using Voicespice Platform in A Speaking Class - Bastian, Arif Alexander; Yunianti, Eka Pratiwi; Ariyani, Erymka (English Education and Literature Journal (E-Jou), 2025)
This study aims to evaluate the effectiveness of VoiceSpice as a language-learning tool, focusing on its usability, advantages, limitations, and overall impact on students' speaking practice by the students’ perceptions. Moreover, much of the current literature focuses on quantitative measures or general outcomes, leaving a gap in understanding students' personal experiences and challenges with recording technology. Without exploring these individual perspectives, it is difficult to address the barriers that may prevent students from fully leveraging these tools for reflective and autonomous learning. The sample in this study consisted of 15 EFL students who studied English at Universitas Aisyah Pringsewu. Data was collected through observation to get a direct picture of the learning activities carried out, then questionnaires were given to all students and to get more in-depth information, after that doing interview were conducted with 15 students. The survey and feedback results indicate that voice recording has proven to be a useful tool for supporting speaking practice in language learning, with user feedback indicating ease of use, convenience, and support for speaking skill development. The conclusion of VoiceSpice has demonstrated its utility in supporting speaking practice, with users praising its ease of use, convenience, and positive impact on speaking skills. While effective for basic language practice, limitations such as unstable sound quality and the absence of advanced features, including pronunciation checking, were noted. This study suggests that improvements in audio quality and the addition of accuracy-checking features could enhance its effectiveness and usability